Responses of Critically Endangered migratory Swift Parrots to variable winter drought. (1st December 2016) - Saunders, Debra L.; Cunningham, Ross; Wood, Jeff; Heinsohn, Robert
Abstract: Migratory birds spend a large proportion of their lives within non-breeding habitats. However, knowledge of how they respond to variable winter resources is limited, especially for small migratory species. Citizen science programs provide an effective way to collect data on small migrants over large spatio-temporal scales. Here we present survey data for the Critically Endangered Swift Parrot ( Lathamus discolor ) that were collected by hundreds of volunteers over 7 years across the species' winter range. Swift Parrots were detected in 23% of the 4035 surveys. Linear mixed models were used to examine variation in Swift Parrot abundance and correlations with climate variables. During non-drought years Swift Parrots concentrated within Victorian habitats. However, when Victoria was in drought, the response of the birds depended on the extent of drought conditions throughout the winter range. Consecutive years of drought in Victoria resulted in the population migrating over 1000 km further to drought refuge habitat in New South Wales. This study provides a rare demonstration of the large spatio-temporal responses of a migratory bird population to extreme climate conditions across its winter range. It demonstrates both variable and repeated use of winter habitats, and highlights the need for conservation management at large spatio-temporal scales.